2021
DOI: 10.1007/s12185-021-03126-6
|View full text |Cite
|
Sign up to set email alerts
|

Target spectrum of the BCR-ABL tyrosine kinase inhibitors in chronic myeloid leukemia

Abstract: BCR-ABL1 plays a key role in the pathogenesis of chronic myeloid leukemia (CML), and it has been investigated as a druggable target of tyrosine kinase inhibitors (TKIs) over two decades. Since imatinib, the first TKI for anti-cancer therapy, was successfully applied in CML therapy, further generation TKIs and a novel allosteric inhibitor targeting the myristate binding site have been developed as alternative options for CML management. However, significant concerns regarding toxicity profiles, especially in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…In addition to BCR-ABL1, CML TKIs have distinct inhibitory activities to other kinases and the differences in substrate spectrum might contribute to their various cardiovascular toxicities. Previous studies reveal that SRC kinase and FGFRs are common targets for ponatinib, dasatinib and bosutinib but they are not inhibited by imatinib and nilotinib (Moslehi and Deininger, 2015;Rossari et al, 2018;Zeng and Schmaier, 2020;Lee et al, 2021) which is consistent with our observation that ponatinib, dasatinib, bosutinib but not imatinib and nilotinib induce dorsal aorta stenosis in zebrafish (Figure 1B), so we hypothesized that inhibition of SRC or FGFRs is involved in the vasculopathies of CML TKIs. We investigated this hypothesis by testing the effect of SRC inhibitor (Src-IN-1) or FGFR inhibitor (infigratinib) on vessel integrity.…”
Section: Src Inhibition Contributes To Vascular Toxicity Of CML Tkissupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to BCR-ABL1, CML TKIs have distinct inhibitory activities to other kinases and the differences in substrate spectrum might contribute to their various cardiovascular toxicities. Previous studies reveal that SRC kinase and FGFRs are common targets for ponatinib, dasatinib and bosutinib but they are not inhibited by imatinib and nilotinib (Moslehi and Deininger, 2015;Rossari et al, 2018;Zeng and Schmaier, 2020;Lee et al, 2021) which is consistent with our observation that ponatinib, dasatinib, bosutinib but not imatinib and nilotinib induce dorsal aorta stenosis in zebrafish (Figure 1B), so we hypothesized that inhibition of SRC or FGFRs is involved in the vasculopathies of CML TKIs. We investigated this hypothesis by testing the effect of SRC inhibitor (Src-IN-1) or FGFR inhibitor (infigratinib) on vessel integrity.…”
Section: Src Inhibition Contributes To Vascular Toxicity Of CML Tkissupporting
confidence: 92%
“…Biochemical studies of target spectrum indicates that imatinib is the most specific CML TKI and it does not inhibit VEGFR signaling; on the other hand, ponatinib has the broadest substrate spectrum as it inhibits FGFRs, VEGFRs, PDGFRs, KIT, SRC, TIE2, etc. in addition to ABL (( Moslehi and Deininger, 2015 ; Zeng and Schmaier, 2020 ; Lee et al, 2021 ). The ability to suppress VEGFR signaling is consistent with its potential cardiovascular toxicity in ponatinib, however, such correlation does not exist in other TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, 40%-60% of patients who attained deep and durable molecular responses successfully maintained remission after TKI discontinuation. 12 , 22 , 23 , 68 Numerous studies have identified correlations between TFR and the cellular immune system, including a higher number of NK cells and a lower Treg proportion, as previously mentioned, compared with patients who show disease relapse or transformation, suggesting that TFR is based on immune regulation and should be considered to identify promising immunotherapeutic targets, allowing more patients to achieve successful TKI cessation. 81 , 82 , 91 , 92 However, to further evaluate the impact of the immune system on TFR, additional immunological parameters must be studied, preferably quantified, to determine the optimal therapeutic endpoint for successful TFR.…”
Section: What Is a Better Methods Of Management?mentioning
confidence: 90%
“…3,18 On the one hand, the cytoplasmic location advantage of the BCR-ABL oncoprotein allows it to access many cell substrates that are not accessible by major nuclear ABL proteins, which regulate the activation of survival and proliferation pathways, 19 such as RAS/STAT5/PI-3K. [20][21][22][23] On the other hand, growing evidence exists that uncontrolled activation of BCR-ABL is directly linked to the genetic instability observed in disease progression, initiated by reactive oxygen species (ROS) and oxidative DNA damage. BCR-ABL kinase activity seems to promote various DNA repair mechanisms but with inefficient, unfaithful DNA repair in return, facilitating the accumulation of additional cytogenetic abnormalities that cause irreversible changes in the phenotype of CML-CP cells toward that in BP and selection of BP clones.…”
Section: Evidence That Drives CML Progression Is Increasingly Explored At Different Molecular Levelsmentioning
confidence: 99%
“…The usage of KIs in the treatment of several leukemia subtypes is an already established course of action in clinical practice. CML, FMS-like tyrosine kinase 3 (FLT3)-mutated AML and B-cell neoplasms are amongst the malignancies most responsive to KI treatment, including FDA approved drugs [ 73 , 74 , 75 ].…”
Section: Recent Prospects Into Clinical Investigationsmentioning
confidence: 99%